Rethinking leadership education: narrative inquiry and leadership stories. Issue 5 (3rd September 2017) - Damiani, Jonathan; Rolling, James Haywood; Wieczorek, Douglas
Abstract: This narrative essay shares observations and insights about how instructors can use creativity, student voice, and personalized learning to create more responsive educational leadership pedagogy. Three stories, as told by a professor and two former students, explore how students' narratives can naturally inform educational leadership preparation across international borders. We aim to demonstrate how students' narrative experiences in education can contribute to exisiting discourse and research on effective and innovative pedagogical practice in educational leadership preparation.